A new genus and species of Platyischnopidae (Amphipoda: Gammaridea) from the Argentine Sea, South-West Atlantic Ocean - Chiesa, Ignacio L.; Alonso, Gloria M. (Zootaxa, 2014)
The family Platyischnopidae is herein reported for the first time in the Argentine Sea, South-West Atlantic Ocean. A new genus and species, Platyisao holodividum gen. et. sp. nov., collected off the coast of Buenos Aires and Río Negro provinces, is fully described and illustrated. Platyisao gen. nov. is distinguished from the eight other genera of Platyischnopidae by the gnathopods subchelate, and the telson elongate, completely cleft. In addition, the distribution of Tiburonella viscana (Barnard J.L., 1964), up to now known in the South-West Atlantic Ocean from Brazilian waters, is extended to the coast off Buenos Aires province, Argentina.